Up-to-date public order and Actors in its development - Rahmouni, Idriss; Rikli, Seddik (Journal of Human Sciences, 2023)
The circle of traditional triad of public order has been expanded to include other elements introduced acording to the evolution of society’s perceptions and aspirations, and increasing the scope of the state’s intervention in various social, economic and other matters, and each of the three authorities plays its role whithin the path of developing elements of public order, and the judiciary has a prominent role to play in determining the independent existance of new elements, it consists publicmoralorder, social and economic order, and aesthetic public order, thispaper concluded that the list is open to the emergence of other elements that reflect the evolution of society, the state’s view of defferent aspects of life and the extent to which they can be interfered with an accordance with the circumstance of time and space.